Initial experiences with extracorporeal shock wave therapy for treatment of bone spavin in horses – part II - McCarroll, G. D.; McClure, S. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
Extracorporeal shock wave therapy (ESWT) has grown from the original use of treating urinary calculi into a mechanism to treat some specific orthopaedic diseases of humans and animals. This paper describes a group of horses with bone spavin treated with ESWT. Horses were treated with a high energy focused shock wave machine. Horses were examined for lameness pre-treatment and 12 weeks post-treatment. There was a decrease in the lameness of 80% (59/74) of the horses treated. ESWT provides a viable noninvasive mechanism of treating refractory bone spavin in the horse.
Keywords: Shockwave therapy; bone spavin